The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/0103-8478cr20190363
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of various plant extracts and their in vitro efficacy in control of Fasciola hepatica eggs

Abstract: Fasciolosis has been diagnosed in cattle, goats, sheep and horses in southern and southeastern Brazil. Effective alternative treatments are the targets of study. One promising alternative is the use of plant extracts. The aim of this study was to perform phytochemical analysis of extracts of Eugenia uniflora L., Harpagophytum procumbens, Psidium guajava L. and Stryphnodendron adstringens, and to evaluate the in vitro efficacy of these extracts on ovicidal activity in Fasciola hepatica. Plant extracts were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Miracidia maturation occurs within 12-16 days in eggs of both F. hepatica and F. gigantica regardless of the host species [16]. Several reports showed that the chemical composition of various plant extracts [19] could penetrate the eggshell and inhibit the egg hatching depending on the solubility in lipids [20]. Also, albendazole and triclabendazole ovicidal activity against F. hepatica eggs and the inhibitory effects of these compounds on the hatching process has been observed [21].…”
Section: Discussionmentioning
confidence: 99%
“…Miracidia maturation occurs within 12-16 days in eggs of both F. hepatica and F. gigantica regardless of the host species [16]. Several reports showed that the chemical composition of various plant extracts [19] could penetrate the eggshell and inhibit the egg hatching depending on the solubility in lipids [20]. Also, albendazole and triclabendazole ovicidal activity against F. hepatica eggs and the inhibitory effects of these compounds on the hatching process has been observed [21].…”
Section: Discussionmentioning
confidence: 99%
“…Other plants possessing ovicidal activities in vitro to Fasciola eggs are E. uniflora L. H. procumbens, P. guajava L., S. adstringens and Z. officinale [25,26]. Almost all of the plants tested contain phenolic compounds, tannins and terpenes [26]. The significant results of this study may indicate further experiment necessary which is focus on lower concentrations and bioactive analysis of the ethanolic extract.…”
Section: Resultsmentioning
confidence: 77%
“…Another study showed that embryonated F. gigantica eggs are more susceptible to ethanolic extract of Moringa oleifera leaf than the non-embryonated eggs [17]. Other plants possessing ovicidal activities in vitro to Fasciola eggs are E. uniflora L. H. procumbens, P. guajava L., S. adstringens and Z. officinale [25,26]. Almost all of the plants tested contain phenolic compounds, tannins and terpenes [26].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro tests have been carried out by various researchers around the world, seeking to support choices of drugs to be used routinely be breeders and contribute to the diagnosis of F. hepatica resistance. Some authors in Brazil have also carried out in vitro studies using plant extracts ( Marques et al, 2020 ), essential oils ( De Mello et al, 2023 ; Silva et al, 2020b ) and helminthophagous fungi ( Dias et al, 2013 ), seeking alternative forms to control F. hepatica adults or eggs.…”
Section: Controlmentioning
confidence: 99%